Development of Mini Silk Screen Printing Machine - SHAFEI, SUZANA; Mohd Hairol Mizzam Bin Haris; Mohd Nubli Bin Ahmat (Politeknik Aceh, 2024)
The research aims to develop and design a mini semi-automatic screen-printing system that can be easily controlled. The objectives of this project are to create a suitable design for the mini semi-auto screen printing system and to develop it accordingly. The type of study conducted is the development of a real project, which is the production of a mini silk screen printing machine. The development of this project involves 4 phases: design and fabrication phase, motor wiring system, mould production and testing process. In this project, a mechanical setup will be created to execute the printing process. This setup will include a conveyor mechanism to hold the paper, a lifting arrangement, a wiping setup, and cutters. To control the printing operation and semi-automate the screen-printing setup, a power panel will be utilized. The setup will encompass a control system and a motion system, which will consist of a gear assembly and servo motors. The testing conducted is the functional process of the system regarding machine operation. As a conclusion, the development of mini silk screen printing successfully develops for student in Mechanical Engineering Department in POLIMAS. Keywords: Silk screen printing, printing process, control system